DETERMINATION OF GENUINE OWN INCOME, PROFIT-SHARING FUNDS, GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS AND SILPA ON CAPITAL EXPENDITURES IN 5 CITIES IN ACEH PROVINCIAL GOVERNMENT IN 2012-2021 - Widya Ningrum; Chairil Akhyar; Nurlela; Halida Bahri (PT. Radja Intercontinental Publishing, 2023)
This study aims to determine the Determination of Regional Original Income, Profit Sharing Funds, General Allocation Funds, Special Allocation Funds and Silpa on Capital Expenditures in 5 Cities in the Provincial Government of Aceh in 2012-2021. The data used in this study are secondary data of 50 observations. . The method used to analyze the relationship between the independent variables and the dependent variable is panel data regression analysis. The results of the study show that local revenue has a positive effect on capital expenditure in 5 municipal governments in Aceh Province, revenue sharing has no effect on capital expenditure in 5 municipal governments in Aceh Province. General allocation funds have a negative effect on capital spending in 5 municipal governments in Aceh Province. Special allocation funds have a positive effect on capital spending in 5 municipal governments in Aceh Province. Silpa has no effect on capital expenditure in 5 municipal governments in Aceh Province.